Sintesis Turunan Eusiderin A dan Evaluasi Aktifitas Antimakan terhadap Hama Tanaman, Epilachna sparsa - Syamsurizal Syamsurizal; Afrida Afrida (Jurnal Matematika & Sains, 2009)
Eusiderin A(1) which isolated from bulian wood (Eusideroxylon zwagery) was converted into five congeners (2- 6) which designed on account of the clogP smaller than 1. The structures of these five compounds were determined based on their spectroscopic data including 1H- NMR, 1H-1H-COSY, and NOESY spectra and mass spectra. The antifeedant activity and the brine shrimp lethality test against Artemia salina were evaluated to demostrate that 2, 3 and 6 increased significantly the antifeedant activity than eusiderin A, while the compounds(2-6) were classified as non toxic.